UNDERSTANDING PRODUCTIVE ZAKAT DISTRIBUTION PROGRAM APPROACH IN INDONESIA: STUDY FROM BAZNAS KUNINGAN REGENCY - Jamal, Haerul; Suryadi, Suryadi; Turasih, Turasih (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2023)
This study aims to understand the program approach is used in the distribution of productive zakat funds carried out by BAZNAS Kuningan Regency. This study uses descriptive qualitative methods, data collection techniques of interviews, observation and documentation. The results of the study show that the program approach taken by BAZNAS of Kuningan Regency in distributing productive zakat funds is to use a technical assistance approach. This is due to several reasons, including the first, the role of the program assistant as an expert and adviser through regular training and mentoring activities with mustahik. Second, the way the program works is top down in which this program has been designed by the Central BAZNAS to be implemented at regional BAZNAS. Third, the participation of mustahik in the program is limited because needs and problem assessment, program planning and design, as well as monitoring and evaluation are carried out by BAZNAS without involving mustahik. mustahik are only recipients and connoisseurs of the program. Fourth, program achievements and changes in mustahik economic conditions occur in a fast time. BAZNAS must be careful because even though changes occur quickly, this approach is very prone to causing mustahik dependence on the program